Migration of Near Earth Asteroid to Jovian-Crosser Asteroid : Case Study 3552 Don Quixote - Suryadi Siregar (Jurnal Matematika & Sains, 2010)
It is generally recognized that main-belt asteroids (MBAs) and nuclei of extinct comets are the two main sources for the Near-Earth-Asteroids (NEAs). Theoretical studies of NEAs dynamics and numerical modelling of their orbital motions showed that the resonance mechanism for supplying NEAs is quite sufficient to sustain this population. Asteroid 1983 SA, also known as 3552 Don Quixote, is one of Near Earth Asteroids (NEAs) and the most probable candidates for NEAs of the cometary origin. In this work, an investigation on the evolution of the orbit is done by using the SWIFT subroutine package, where the gravitational perturbations of eight planets: Mercury, Venus, Earth, Mars, Jupiter, Saturn, Uranus, and Neptune are considered. Migration of asteroid 3552 Don Quixote from Near Earth Asteroids (NEAs) to Jovian-crosser asteroid is found.